Clark transportation hub - Te, Chelsea Mae P.
The inefficiency in transport infrastructures in Metro Manila has increasingly become a problem in the city, resulting in traffic congestions and loss of revenues. A transport terminal away from the capital will act as a supporting terminal for the Disodado Macapagal International Airport in Clark. The development will provide transportation options for the tourists arriving in the city, and for the local residents of Clark. In addition, the hub consists of services which will support the operations of the airport, services such as a hostel for overnight visitors and a duty free shop for the locals and tourists.